Connecting Metabolic Pathways: Sigma Factors in Streptomyces spp. - Sun, Di; Liu, Cong; Zhu, Jingrong; Liu, Weijie (Frontiers in Microbiology, 2017)
The gram-positive filamentous bacterium Streptomyces is one of the largest resources for bioactive metabolites, particularly antibiotics. Antibiotic production and other metabolic processes are tightly regulated at the transcriptional level. Sigma (σ) factors are components of bacterial RNA polymerases that determine promoter specificity. In Streptomyces, σ factors also play essential roles in signal transduction and in regulatory networks, thereby assisting in their survival in complex environments. However, our current understanding of σ factors in Streptomyces is still limited. In this mini-review, we demonstrate the roles of Streptomyces σ factors, illustrating that these serve as linkers of different metabolic pathways. Further investigations on σ factors may improve our knowledge of Streptomyces physiology and benefit exploitation of Streptomyces resources.